ANTIHYPERLIPIDEMIA EFFECT OF SAGA TREE LEAF ETHANOL EXTRACT (Adenanthera pavonina L.) ON MENCIT (Mus musculus) - Sofia Ayu Fernanda; Khoirul Ngibad (Universitas Negeri Yogyakarta, 2025)
There is no consensus on the optimal dosage and mechanism of action of saga leaf ethanol extract in lowering cholesterol levels in test animals; therefore, further research is needed to understand the effectiveness and optimal dose of this plant as a hyperlipidemia therapy. This study aims to determine the optimal dose of ethanol extract from the leaves of the saga tree (Adenanthera pavonina L.) in reducing cholesterol levels in hyperlipidemic mice. The study was conducted on 36 male mice that were acclimatized for 7 days and induced hyperlipidemia using Propylthiouracil. The test animals were divided into six treatment groups, including a negative control, a positive control, a drug control (simvastatin), and three treatment groups with extract doses of 14, 28, and 56 mg/20 g body weight (BW). Cholesterol levels were measured using the spectrophotometry method, and the data were analyzed using the ANOVA test. The results of the ANOVA test showed a significance value of 0.000 (p < 0.05), indicating a difference in cholesterol levels between groups. A dose of 56 mg/20 g BW showed the highest reduction in cholesterol levels of 57.87 mg/dL. It was concluded that the ethanol extract of the leaves of the saga tree was effective in reducing the cholesterol levels of hyperlipidemic mice at an optimal dose of 56 mg/20 g BW. These results show the potential of the extract as a natural antihyperlipidemia agent that can be developed into an alternative cholesterol-lowering therapy.